2009
DOI: 10.1152/jn.90696.2008
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Optical Images of Cortical Responses for Inferring Functional Maps

Abstract: Purushothaman G, Khaytin I, Casagrande VA. Quantification of optical images of cortical responses for inferring functional maps. J Neurophysiol 101: 2708 -2724, 2009. First published February 18, 2009 doi:10.1152/jn.90696.2008. Optical imaging of cortical signals enables the mapping of functional organization across large patches of cortex with good spatial resolution. But techniques for the quantitative analysis and interpretation of these images are limited. Frequently the functional architecture of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…In contrast, more recent techniques with single cell resolution (Ohki et al, 2006) only allow mapping a surface on the order of two to three PCs simultaneously (Nauhaus et al, 2013). Second, previous studies based on electrophysiology have concluded that preferred SF is only weakly clustered among neighboring neurons in the visual cortex of felines (DeAngelis et al, 1999) and bush babies (Purushothaman 2009). Our own electrophysiological data (see Fig.…”
Section: At Which Spatial Scale Pinwheel-dipoles Appear?supporting
confidence: 47%
“…In contrast, more recent techniques with single cell resolution (Ohki et al, 2006) only allow mapping a surface on the order of two to three PCs simultaneously (Nauhaus et al, 2013). Second, previous studies based on electrophysiology have concluded that preferred SF is only weakly clustered among neighboring neurons in the visual cortex of felines (DeAngelis et al, 1999) and bush babies (Purushothaman 2009). Our own electrophysiological data (see Fig.…”
Section: At Which Spatial Scale Pinwheel-dipoles Appear?supporting
confidence: 47%
“…Single-condition maps were computed by comparing whether reflectance changes evoked by a single-stimulus condition could be discriminated from reflectance changes evoked across all presented stimuli 42 . To discriminate a single-condition stimulus at each pixel, reflectance changes across all stimuli were combined into a normalized histogram, and then a pixel’s single condition response was computed non-parametrically as the probability of the area under a ROC curve (using the trapezoidal rule).…”
Section: Methodsmentioning
confidence: 99%
“…For the population average choice probability of 0.55, at least 100 trials were required for the odd and even estimates to differ by less than 0.05 (i.e., 0.55–0.5). A different empirical approach was required to estimate the number of trials required to significantly reduce estimation errors in the ROC analysis of optically imaged intrinsic signals (Purushothaman et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Parker and Newsome, 1998). Ideal observer analysis can also be applied to optically imaged cortical signals to assess neural population sensitivity for detection or discrimination (Chen et al, 2006, 2008; Purushothaman et al, 2009; see also rev: Cohen et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation